A case of Candida albicans fungus balls in the urinary tract appeared during the course of antifungal treatment for Candida endophthalmitis. Issue 9 (September 2015) - Onozawa, Kyoko; Miyake, Noriko; Iwasaki, Noriko; Nishida, Ruriko; Chong, Yong; Shimoda, Shinji; Shimono, Nobuyuki; Akashi, Koichi
Abstract Fungus balls have been rarely implicated as a cause of urinary tract obstruction. Here, we report a case of Candida albicans fungus balls in the urinary tract after the treatment of Candida endophthalmitis that has enough periods and adequate amount of antifungal agents. The patient completely recovered from this rare complication by irrigating through single-J stent and changing antifungal agents. Here we emphasize that we should take into account not only the susceptibility test results but also the difference in excretion route and tissue distribution of antifungal agents.